An Exploration of Pro-Environmental Values in Learning: A Case Study in Elementary Schools - Rintoni, Rintoni; Hakam, Kama Abdul; Yudianto, Suroso Adi; Warlim, Warlim (Mimbar Sekolah Dasar, 2025)
Pro-environmental values are crucial to instill in students to foster a generation that cares about the environment, promoting sustainability through education. Teachers play a central role in developing students' morals, encouraging responsible behavior and pro-environmental attitudes. This study explores pro-environmental values in ecology learning, focusing on ecosystem balance and the potential for more effective ecological education. Conducted at an elementary school in Subang Regency, West Java, it involved teachers and sixth-grade students. Using a qualitative case study approach, data was collected through observation, interviews, and discussions with 21 respondents, including principals, teachers, and students. Analysis followed stages of data collection, reduction, display, and conclusion. The study identified six key pro-environmental values taught: 1) environmental education, 2) energy-saving and renewable energy, 3) waste reduction, 4) anti-consumerism, 5) recycling, and 6) nature conservation. These values enhance students' capacity to act sustainably, fostering environmentally friendly behavior and responsible character. The findings underscore the importance of integrating pro-environmental values into ecological teaching to build environmentally conscious students. This study contributes to understanding how ecological learning materials can effectively promote sustainability, equipping teachers with tools to nurture environmentally aware future generations.